The Effects of Market Diversification Activities on Bangladesh RMG Export - Ahmed, Redwan; Islam, Md. Tawhidul; Al-Amin, Md. (International Journal of Economics and Financial Issues, 2013)
This study evaluates the role of market diversification activities conducted mostly from 2007 to 2011 on RMG export value through exploring more promising destinations for apparel export as well as inventing newer clothing products. Trend analysis approach has been followed to analyze statistical information which was mostly collected from secondary sources, especially from ITC Trade Map, EPB Bangladesh, and BKMEA’s Database. The ten years long time period is divided equally into two phase namely Pre-intervention period from 2002 to 2006 and Intervention period from 2007 to 2011 to contrast the effects of trade promotional activities on apparel export earnings. Theses promotional activities culminated to access into 62 newer markets developing 30 more RMG products. Moreover, the increment in export value by US4056.87 million in 2011 compared with that in 2002 demonstrates the positive effects of on apparel export. Keywords: Monopsony; GSP JEL Classifications: F13; F14